Bridging Popularity and Poverty: A Policy Analysis of Empowering Coffee Farmers in Bener Meriah, Indonesia - Amanda, Deya; Latif, Ikhwan Rahmatika; Cibro, Karina; Saputra, Ilham Mirza; Fahlevi, Reza (Jurnal Pemerintahan dan Kebijakan (JPK), 2026)
The contrast between the global acclaim of Gayo Arabica coffee and the ongoing impoverishment of its growers in Bener Meriah Regency, Indonesia, underscores a significant deficiency in policy execution. This study seeks to evaluate the implementation of the local coffee farmer empowerment policy, based on Qanun No. 16 of 2016 and executed by the Department of Agriculture and Food. Data were gathered utilizing a qualitative case study methodology, employing in-depth interviews and document analysis. Thematic analysis was performed utilizing George C. Edwards III’s policy implementation model, concentrating on four variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that although government implementers have exhibited significant dedication and human resource competence, the program faced obstacles due to inconsistent communication, insufficient physical infrastructure, limited farmer engagement, and poor coordination with village-level organizations. The limitations constrained the policy’s efficacy in converting conventional coffee processes into more lucrative post-harvest processing. The persistence of structural and contextual constraints reduced the program’s capacity to improve farmers’ welfare and contributed to the continuation of existing disparities. Recommendations encompass enhancing localized communication, investing in critical infrastructure, offering transitional incentives, and facilitating more adaptive and participatory implementation frameworks.